Disparity in Political Participation in the Local Bodies: A Case Study of Ranchi (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Government is the field of politics, which also encompasses issues of representation, policy, authority, and prestige. By "political participation," we mean people's active engagement in government. It makes sure that everyone has a voice in determining society's overarching objectives and the most effective means of accomplishing those goals. Taking part in politics involves more than just casting a ballot; it involves contributing to the decision-making, policymaking, and distribution of power at all levels of government. This study has been carried out to find out the variation of political participation of the women in respect of the variables-age, marital status and educational qualification. A field study was conducted across five districts of Jharkhand in order to study the nature of political participation of elected women representatives in local bodies of the state. Five districts covered during the field study were Ranchi, Hazaribagh, Gumla, Lohardaga and Khunti. A finding of the study concludes that age is a vital factor for women to enter politics and Women with Higher Education are present at the grass-root level institutions in the state.